Methyl 2-(benzenesulfonamido)acetate - Arshad, Muhammad Nadeem (International Union of Crystallography, 2009)
The title compound, C(9)H(11)NO(4)S, is of interest as a precursor to biologically active benzothiazines. The crystal structure is stabilized by intermolecular N—H⋯O and C—H⋯O interactions.